Greenhouse gas emissions mitigation and economic viability of sugar crops in China - Linsheng YANG; Xiaozhong WANG; Wushuai ZHANG; Prakash LAKSHMANAN; Yan DENG; Xiaojun SHI; Xinping CHEN; Fusuo ZHANG (Frontiers of Agricultural Science and Engineering)
● Sugarcane and sugar beet yield and carbon footprint rose with time but profit declined ● Labor and nitrogen fertilizer were the largest contributors of carbon footprint. ● Optimized crops lowered carbon footprint and total cost by 32% and 24%, respectively. Climate change mitigation is a major challenge of human society. Currently, to this end, many countries including China are committed to achieving carbon neutrality within a few decades. China is a major sugarcane and sugar beet producing country and has one of the largest carbon footprint for sugarcane and sugar beet production globally. A comprehensive study was conducted on sugarcane and sugar beet crops grown in China for greenhouse gas (GHG) emissions mitigation potential, economic crop production from a sustainable sugar production perspective. Long-term trend analysis showed that yield and GHG emissions of sugarcane and sugar beet crops increased but the ratio of income to cost declined. Structural equation model analysis revealed nitrogen fertilizer and labor as the major drivers of GHG emissions for both sugarcane and sugar beet. For sugarcane and sugar beet, the path coefficient of N fertilizer were ‒0.964 and ‒0.835 and that of labor were 0.771 and 0.589, respectively. By transitioning the current cropping system to an improved model with optimized labor, N input and machinery use, the GHG emissions and total annual cost of sugarcane and sugar beet production can be reduced by 32% and 24%, respectively, by 2030, compared to a business-as-usual scenario. This is the first integrated and comparative study of environmental and economic sustainability of sugarcane and sugar beet production in China. These findings will enable all stakeholders of Chinese sugarcane and sugar beet industries to transform them into environmentally and economically sustainable sugar production.